Molecular diagnostics enables detection of actionable targets: the Pediatric Targeted Therapy 2.0 registry - Ecker, Jonas; Selt, Florian; Sturm, Dominik; Sill, Martin; Korshunov, Andrey; Hirsch, Steffen; Capper, David; Dikow, Nicola; Sutter, Christian; Müller, Carina; Sigaud, Romain; Eggert, Angelika; et al. (European journal of cancer, 2023)
Precision oncology requires diagnostic accuracy and robust detection of actionable alterations. The Pediatric Targeted Therapy (PTT) 2.0 program aims at improving diagnostic accuracy by addition of molecular analyses to the existing histological diagnosis and detection of actionable alterations for relapsed paediatric oncology patients, in cases with limited availability of tumour material.
Online veröffentlicht am 25. November 2022, Artikelversion vom 19. Dezember 2022
Gesehen am 22.11.2023